Facile Electrochemical Synthesis of 2D Monolayers for High-Performance Thin-Film Transistors - Schulman, Daniel S; Sebastian, Amritanand; Buzzell, Drew; Huang, Yu-Ting; Arnold, Andrew J; Das, Saptarshi (ACS applied materials & interfaces, 2017)
In this paper, we report high-performance monolayer thin-film transistors (TFTs) based on a variety of two-dimensional layered semiconductors such as MoS2, WS2, and MoSe2 which were obtained from their corresponding bulk counterparts via an anomalous but high-yield and low-cost electrochemical corrosion process, also referred to as electro-ablation (EA), at room temperature. These monolayer TFTs demonstrated current ON–OFF ratios in excess of 107 along with ON currents of 120 μA/μm for MoS2, 40 μA/μm for WS2, and 40 μA/μm for MoSe2 which clearly outperform the existing TFT technologies. We found that these monolayers have larger Schottky barriers for electron injection compared to their multilayer counterparts, which is partially compensated by their superior electrostatics and ultra-thin tunnel barriers. We observed an Anderson type semiconductor-to-metal transition in these monolayers and also discussed possible scattering mechanisms that manifest in the temperature dependence of the electron mobility. Finally, our study suggests superior chemical stability and electronic integrity of monolayers even after being exposed to extreme electro-oxidation and corrosion processes which is promising for the implementation of such TFTs in harsh environment sensing. Overall, the EA process proves to be a facile synthesis route offering higher monolayer yields than mechanical exfoliation and lower cost and complexity than chemical vapor deposition methods.